PENGARUH TIME PRESSURE, AUDIT RISK, MATERIALITY, REVIEW PROCEDURES AND QUALITY CONTROL TERHADAP PREMATURE SIGN OFF DENGAN LOCUS OF CONTROL SEBAGAI VARIABEL MODERATING (Studi Empiris Pada BKP-RI Perwakilan Provinsi Riau dan Sumatera Barat) - Risma, Fadhilah; Andreas, Andreas; Diyanto, Volta (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Ekonomi, 2017)
The study aimed to examine the effect of time pressure, audit risk, materiality, review procedures and quality control on premature sign off audit procedures moderated by locus of control. The sample of this study are 50 auditors. Data were collected through a survey to auditors in BPK Riau and West Sumatra area by using personally administrated questionnaires. Writer tested the quality of data that included validity test and reliability test, normality test, asumsi klasik test, and use the hypothesis by means of multiple regression analysis test, t test and determination coefficient test using program software SPSS. The results of this study found that time pressure, audit risk, materiality, review procedures and quality control variables affect premature sign off and locus of control can moderate the effection of all independent variables with premature sign off.Keywords : premature sign-off, audit risk, time pressure, audit risk, materiality, review procedures and quality control, and locus of control